2021
DOI: 10.1002/ca.23817
|View full text |Cite
|
Sign up to set email alerts
|

Termination points of the facial artery—A meta‐analysis

Abstract: The facial artery (FA) is the main artery supplying the anterior face, making this artery a very important structure to consider while performing plastic and reconstructive procedures. The literature shows discrepancies in anatomical classifications and the frequency of occurrence of individual variations. Therefore, the goal of this meta‐analysis is to provide surgeons with helpful knowledge about the variety of the termination of FA. Articles with data about the termination of the FA were found in major onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 45 publications
(91 reference statements)
0
17
0
Order By: Relevance
“…The literature shows discrepancies in classifications according to the types, incidence, and termination patterns of FA [6] (Table 6). The termination pattern of the FA varies in the literature, including the superior labial (SL), LNA, AA, and others [1,6]. Early termination of the FA has also been reported in the submental, inferior labial (IL), and alar arteries [6].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The literature shows discrepancies in classifications according to the types, incidence, and termination patterns of FA [6] (Table 6). The termination pattern of the FA varies in the literature, including the superior labial (SL), LNA, AA, and others [1,6]. Early termination of the FA has also been reported in the submental, inferior labial (IL), and alar arteries [6].…”
Section: Discussionmentioning
confidence: 99%
“…The termination pattern of the FA varies in the literature, including the superior labial (SL), LNA, AA, and others [1,6]. Early termination of the FA has also been reported in the submental, inferior labial (IL), and alar arteries [6]. Koh et al [24] reported that 54.5% of the 44 specimens were symmetrical.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations